Thermal-motion-induced non-reciprocal quantum optical system. Issue 12 (December 2018) - Zhang, Shicheng; Hu, Yiqi; Lin, Gongwei; Niu, Yueping; Xia, Keyu; Gong, Jiangbin; Gong, Shangqing
Abstract Magnetic-free optical non-reciprocal components, such as isolators and circulators, are highly desirable for on-chip optical signal processing1, 2 and quantum networks3, 4 . However, their realization presents a fundamental difficulty due to the Lorentz reciprocity in most optical devices5 . In this study, we propose and experimentally realize optical non-reciprocity with atoms embedded in a ring cavity at room temperature. Random thermal motion of atoms, in the presence of a unidirectional control field, creates susceptibility–momentum locking, and subsequently a new type of chiral quantum optical system. Furthermore, we demonstrate strong non-reciprocity based on this chiral quantum system in the regime of collectively strong atom–cavity coupling. Our scheme provides a new routine towards the realization of chiral quantum optics and chip-compatible, non-magnetic optical non-reciprocity. Optical non-reciprocity is experimentally realized with Rb atoms embedded in a ring cavity at room temperature. Random thermal motion of the atoms causes the probe-direction-dependent response assisted by a unidirectional control laser field.